Built Environment: Relating The Benefits of Renewable Energy Technologies - Omer, Abdeen Mustafa (Universiti Malaysia Pahang, 2012)

(untitled)
Recently, environmental issues have been the focus of much of the world’s attention. This has stimulated a response in many countries, which has led to a closer examination of energy conservation strategies for conventional fossil fuels. One way of reducing building energy consumption is to design buildings, which are more economical in their use of energy for: heating, lighting, cooling, ventilation and hot water supply. Passive measures, particularly natural or hybrid ventilation rather than air-conditioning, can dramatically reduce primary energy consumption. However, exploitation of renewable energy in buildings and agricultural greenhouses, can significantly contribute in reducing dependency on fossil fuels. Therefore, promoting innovative renewable applications and reinforcing the renewable energy market will contribute to preserving the ecosystem by reducing emissions at local and global levels. This will also contribute to the amelioration of environmental conditions, through a reduction in air pollution and greenhouse gases, by the replacement of conventional fuels with renewable energies.